2021
DOI: 10.17219/acem/143573
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ketamine, thiopental and their combination on the rat liver: A biochemical evaluation

Abstract: Background. In the literature, it has been suggested that ketamine-related oxidative organ damage results from increased blood adrenaline level, and thiopental-related oxidative damage is caused by decreased adrenaline level, suggesting that ketamine-thiopental combination (KT) may be beneficial in reducing the hepatotoxic effect of ketamine.Objectives. To biochemically investigate the effects of ketamine, thiopental and KT on the liver in rats. Materials and methods.Male albino Wistar type rats received intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The risk of hepatotoxicity associated with this drug in children when applied alone is unclear. Bedir et al indicated that oxidative stress and inflammation develop in the liver tissue of rats injected with thiopental alone, but further clinical studies are needed to explore this effect in humans [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of hepatotoxicity associated with this drug in children when applied alone is unclear. Bedir et al indicated that oxidative stress and inflammation develop in the liver tissue of rats injected with thiopental alone, but further clinical studies are needed to explore this effect in humans [ 60 ].…”
Section: Discussionmentioning
confidence: 99%